Творчество Якова Голосовкера в контексте русской и западно- европейской культуры - Biełousowa, Wiera (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2012)
The aim of the present article is to open up the connection of Jakov Golosovker’s creativity with Russian and Western European culture (the Silver Age, Antique culture, German romanticism, German philosophy).
The creativity of Jakov Golosovker in the context of Russian and Western European culture
Twórczość Jakowa Gołosowkera w kontekście kultury rosyjskiej i zachodnioeuropejskiej